2023
DOI: 10.1002/ece3.10499
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of digestive strategies for fishes with different feeding habits: Digestive enzyme activities, intestinal morphology, and gut microbiota

Fang Jiao,
Lei Zhang,
Samwel Mchele Limbu
et al.

Abstract: Fish feeding habit determines the digestive tract structure and intestinal microflora. However, the relationship between feeding habit, digestive intestinal morphology, and microbial diversity of omnivorous, herbivorous, plankton feeder, and carnivorous fish from the same environment has not been compared. This study compared the digestive enzyme activities, intestinal morphology, and intestinal microflora of omnivorous (Carassius auratus), herbivorous (Ctenopharyngodon idellus), carnivorous (Siniperca chuatsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…19 Pseudomonas may help fish digest proteins and most secrete lipases to break down lipids for their own metabolic needs. 20,21 At the secondary functional level, 10 sub-functions related to muscle nutrition were found in the gut microbes of the two groups of tilapias. Correlation analysis showed that the abundance of Pirellu-laceae_unclassified was positively correlated with the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…19 Pseudomonas may help fish digest proteins and most secrete lipases to break down lipids for their own metabolic needs. 20,21 At the secondary functional level, 10 sub-functions related to muscle nutrition were found in the gut microbes of the two groups of tilapias. Correlation analysis showed that the abundance of Pirellu-laceae_unclassified was positively correlated with the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal structure of fish, including their morphology and microstructures, varies with their feeding habits. Several studies have highlighted the direct correlation between these anatomical features and the diet of fish [ 30 ]. Consequently, carnivorous fish like red snapper and opportunistic feeders like Asian seabass require specifically tailored feed ingredients to maintain the optimal functionality of their gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%